2020
DOI: 10.21874/rsp.v71i0.4998
|View full text |Cite
|
Sign up to set email alerts
|

Judicialization of administrative measures to tackle the COVID-19 pandemic in Brazil

Abstract: This article studied the judicialization processes related to the pandemic of the new coronavirus, within the scope of Administrative Law. The cases that reached the Brazilian Federal Supreme Court (FSC), available at the “Painel de Ações COVID-19”, were analyzed, as well as a sample of the cases that reached the state courts, obtained through journalistic reports, consolidated on the “Consultor Jurídico” website. Descriptive analysis and content analysis techniques were used, in the thematic mode, for both so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
1
0
4
Order By: Relevance
“…Figueiredo et. al (14) propuseram a adoção da obrigatoriedade do preenchimento de 46 variáveis no protocolo inicial das ações judiciais em saúde e recomendaram a utilização do formulário padrão do PJe por todos os tribunais brasileiros, para melhorar a classificação e possibilidade de recuperação da informação sobre a judicialização da saúde.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Figueiredo et. al (14) propuseram a adoção da obrigatoriedade do preenchimento de 46 variáveis no protocolo inicial das ações judiciais em saúde e recomendaram a utilização do formulário padrão do PJe por todos os tribunais brasileiros, para melhorar a classificação e possibilidade de recuperação da informação sobre a judicialização da saúde.…”
Section: Discussionunclassified
“…Uma limitação importante da presente análise é que os dados referentes aos anos de 2020 e 2021 podem ter sofrido um impacto significativo da pandemia do COVID-19, seja pelo fato de o trâmite de processos judiciários ter ficado suspenso por vários meses (29), seja pelo surgimento de processos relacionados à própria pandemia (30), ou pelo atraso de inserção de processos no SIGAFJUD pela equipe da SES-MG. Os dados referentes aos anos pandêmicos e pós-pandêmicos merecem análise posterior, para entender o impacto da pandemia no fenômeno da judicialização da saúde.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Conflicts with the economic sector were evidenced by Figueiredo et al 27 , who investigated processes sent to the Supreme Federal Court addressing the COVID-19 issue and found that most (81.4%) of the cases requested decisions on relaxation (permission, closing or limitations on the functioning of trade and transportation), with 54.3% dealing with requests for opening and 45.7% were requests for closing establishments and limitations on the circulation of people.…”
Section: Discussionmentioning
confidence: 99%